Konsekuensi Ontologis dan Politis terhadap Konsep Subjek pada Filsafat Egoisme Max Stirner - Albi Abdullah Maulana Zein; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the ontological and political consequences of the subject in Max Stirner's philosophy of egoism. This research is included in qualitative research, therefore the researcher only conducts a literature study. The results and discussion of this study are that egoism in Max Stirner's thinking is not egoism in the sense of acting for one's own benefit. Stirner's egoism is closer to the notions of self-mastery and self-regulation. Stirner's egoism also needs to be discussed in relation to the concept of the self. The I is this nothingness, so the ‘I’ is not bound by anything, it is unbound and subject to its own morality, rationality, thoughts, even desires. The I must control and master himself so as not to be subdued by those things. Through this concept of the I comes the egotistical subject. The conclusion of this study is that the understanding of Stirner's egoistic subject produces two consequences: ontological and political. Ontological consequences related to the rejection of universality and affirmation of singularity. The political consequence is that politics must be understood as an attempt to reject essentialist identities and generalities.